2023
DOI: 10.1063/5.0182711
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-mechanical water-flow enhancement through a sub-nanometer carbon nanotube

Alberto Ambrosetti,
Pier Luigi Silvestrelli

Abstract: Experimental observations unambiguously reveal quasi-frictionless water flow through nanometer-scale carbon nanotubes (CNTs). Classical fluid mechanics is deemed unfit to describe this enhanced flow, and recent investigations indicated that quantum mechanics is required to interpret the extremely weak water–CNT friction. In fact, by quantum scattering, water can only release discrete energy upon excitation of electronic and phononic modes in the CNT. Here, we analyze in detail how a traveling water molecule co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…3 Meanwhile, Ambrosetti et al reported a critical value of 50 m s −1 , which is described as a requirement to be surpassed with a view to scattering water against CNTs. 60 Concurrently, Ambrosetti et al also pointed towards the straightforward transfer of Landau's criterion of superfluidity, 61 wherein they mentioned the interaction with the quasilinear dispersion of the plasmon and phonon modes and a solid-state analog of the superfluid to be embodied by the (5,5) carbon nanotube. A generalized superfluidity mechanism was also considered for the observed friction suppression over the higher complexity of water.…”
Section: Introductionmentioning
confidence: 99%
“…3 Meanwhile, Ambrosetti et al reported a critical value of 50 m s −1 , which is described as a requirement to be surpassed with a view to scattering water against CNTs. 60 Concurrently, Ambrosetti et al also pointed towards the straightforward transfer of Landau's criterion of superfluidity, 61 wherein they mentioned the interaction with the quasilinear dispersion of the plasmon and phonon modes and a solid-state analog of the superfluid to be embodied by the (5,5) carbon nanotube. A generalized superfluidity mechanism was also considered for the observed friction suppression over the higher complexity of water.…”
Section: Introductionmentioning
confidence: 99%